Agama dan Keberagaman : Sebuah Klarifikasi Untuk Empati - Muawir Haris (TASAMUH: Jurnal Studi Islam, 2017)
In the Matt. 22: 37-40, Yesus said “You shall love the Lord your God with all your heart, and with all your soul, and with all your minds. This is the great and first commandment. And a second is like it, You shall love your neighbor as your self. These two commandments depend all the law and the prophets. The nature of religion has been endlessly discussed by philosophers, theologians, psychologists, and sociologists. They look at different aspects of religion as their interests and their purposes differ. Therefore, they formulate variety of definition of religion. Religion is seen to be difficult to define. But it’s necessary to have a clear definition of religion as a starting point for religious studies. In the globalization era, Muslim needs strong basis theology. Humanist theology is a basis of the world religions. So the question is who the humanist unity of God, as a theology of Quranic? What attitude we must follow in prophetics massage? And than what spirite who guide in association between Ummah in Indonesia country. Idea fundament of humanist unity of God is they have identity of religion and respect to the other. This writing shows that theology (tauhid) is human awareness on thier believer toward the one god which cover it’s one of essence, action, atribute (characteristic). The unity of god essence is a furitification towards God. Yet, The pluralism is to be still unitied with strong bound, namely bound of essence of God. This articel describe the discourse.